Structural and morphogenical characteristics of Italian ryegrass Estanzuela 284 submitted to two intervals between grazing (Research, Society and Development, 2021)
This study was carried out to analyze the influence of different intervals between grazing on the morphogenic and structural characteristics of Italian ryegrass (Lolium multiflorum Lam) cv. Estanzuela 284. The experimental design was completely randomized with two treatments ("FIXO" - pasture occupation at fixed intervals of 28 days and "DEF" - pasture occupation at an interval determined by the time for thermal accumulation equivalent to the duration of ryegrass leaf elongation) and three repetitions. The stocking rate was adjusted to remove 50% of the initial forage mass in each grazing period. The experimental animals were Brangus beef heifers, aged eight months and initial body weight of 150 ±3.9 kg, and a variable number of heifers to regulate the stocking rate. Data were submitted to analysis of variance at a 5% significance level. The intervals between grazing did not affect senescence (TSF), appearance (TAF) and leaf elongation (TEF) rates. The pasture managed with intervals based on the duration of leaf elongation presented a higher percentage of leaves and with the advance of the cycle, a higher leaf: stem ratio. The adoption of fixed intervals between grazing for the management of annual ryegrass pasture is not recommended.